2013
DOI: 10.1111/flan.12025
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Language Student Teaching: Do Supervisor Qualifications Really Matter?

Abstract: According to national standards for foreign language (L2) teacher education programs established by the ACTFL and the Council for the Accreditation of Educator Preparation (CAEP), L2 student teachers must be supervised by university faculty who are qualified L2 educators. An exploratory study was conducted to better understand the impact of content‐specific pedagogical knowledge, L2 experience, and qualifications on the effectiveness of the university supervisor. Its purpose was to compare the beliefs of L2 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The implication for the TC's experiential growth is that site and placement selection with a CT should be purposeful and in keeping with WLTD goals and standards of student achievement. Similarly, García et al (2019) reported professional insularity due to the ostensibly arbitrary CT selection by non-WLTD stakeholders and CTs' lack of knowledge of who the field supervisor was and what his/her qualifications were (see also Kissau & Algozzine, 2013).…”
Section: Ct Relationshipsmentioning
confidence: 99%
“…The implication for the TC's experiential growth is that site and placement selection with a CT should be purposeful and in keeping with WLTD goals and standards of student achievement. Similarly, García et al (2019) reported professional insularity due to the ostensibly arbitrary CT selection by non-WLTD stakeholders and CTs' lack of knowledge of who the field supervisor was and what his/her qualifications were (see also Kissau & Algozzine, 2013).…”
Section: Ct Relationshipsmentioning
confidence: 99%
“…Due to competing demands and university‐, program‐, and department‐wide constraints, it is not surprising that fewer than half of the respondents also supervised candidates’ PreK–12 field experiences and its impact on WLTD (Kissau & Algozzine, ). The MIs who reported being fortunate to be involved in selecting cooperating teachers and practicum sites nevertheless voiced concerns about the availability of quality cooperating teachers and supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…When defining PCK, most studies referred to Shulman (1986;1987), who defined PCK as "that special amalgam of content and pedagogy that is uniquely the province of teachers, their own special form of professional understanding" (Shulman, 1987: 8). Only Kissau and Algozzine (2013) used the term PCK without referring to Shulman nor defining PCK. Luo (2004) only referred to Shulman, but did not define PCK.…”
Section: Rq1: How Is Pck Conceptualized In Empirical Research On Fl/l2 Education?mentioning
confidence: 99%
“…One article focused on Spanish (Hlas & Hildebrandt, 2010), and one on French (van Compernolle & Henery, 2014). Five articles addressed a combination of languages: Spanish, French and German (Kissau & Algozzine, 2013;Watzke, 2007); English, Latin, French, German and Dutch (Meijer et al, 1999;2002), and Spanish, French, German, Italian and Portuguese (Wilbur, 2007). Most studies (n=11) focused on language learning in general.…”
Section: Rq2: How Is Pck Studied In Empirical Research On Fl/l2 Education?mentioning
confidence: 99%
See 1 more Smart Citation